Wellness tourism attributes and tourist outcomes: an analysis of configurational effects - Al-Ansi, Amr; Kim, Seongseop (Sam); Xu, Yuchen; Chen, Che; Chua, Bee-Lia; Han, Heesup (Sage Publications, Inc., 2024)
Prior studies have identified the complexity involved in explaining the relationship between wellness tourism attributes and tourist behavior. This study investigated the configurational effects of 10 constructs in predicting the ambiguous area between overall satisfaction and destination behavioral loyalty. To achieve this, the study used a fuzzy set qualitative comparative analysis (fsQCA) and necessary condition analysis (NCA). The results of the fsQCA generated a range of models that effectively predicted tourists’ high or low levels of overall satisfaction and behavioral loyalty. Furthermore, the NCA results identified perceived quality as an essential construct for achieving the combination of overall satisfaction and behavioral loyalty. The study enhances our current knowledge by broadening our comprehension of the intricate aspects of tourists’ decision-making processes and the formation of their behaviors. Additionally, it provides a roadmap for the industry to effectively address challenges in managing wellness tourism resources.